Near Field Communication (NFC)-Based Prepaid Smart Power Meter - Syamsir, Hendri Novia; Zahra, Sheila; Wijaya, Yusmar Palapa (SHM Publisher, 2024)
An essential part of an electric energy service is an electrical power meter. Numerous customers have already expressed dissatisfaction over the electric meter's faulty readings. The development of an electrical power meter with an NFC reader is presented in this study. When an NFC card is successfully scanned by the NFC reader, the power meter is turned on and ready to deliver electricity. Before the electricity is automatically turned off, or when the credit is almost low, the display will show the alert. By experiment, PZEM 004T sensor use 3 loads, namely 60 W, 75 W and 100 W for testing current, voltage and cos phi and have error of 0 – 1.20%. In balance reduction with loads of 60 W, 75 W, and 100 W with a time gap of 5 and 10 minutes, there is an error reduction of 11.5 – 17.4%. Thus, this electricity meter with NFC reader is suitable for monitoring and controlling electricity usage.